KERJA SAMA KELEMBAGAAN PADA MADRASAH ADIWIYATA DI MTS NEGERI 2 PAMEKASAN - Ali Nurhadi; Irfaida Irfaida (Prodi MPI Fakultas Tarbiyah IAIN Madura, 2018)
Madrasah is a formal institution that aims to develop and enhance individual potential, both physical and psychological potential. Madrasah programs can only run smoothly if they receive community support. Therefore, madrasah leaders need to continuously foster good relations between madrasah and the community. Realizing the adiwiyata madrasah program must be supported by cooperation between the community and the madrasa to support the achievement of the program. Based on this research was carried out in the form of a case study of institutional cooperation at the adiwiyata madrasah in MTs Negeri 2 Pamekasan with three research focuses, namely: 1) Implementation of institutional cooperation in adiwiyata madrasah at MTs Negeri 2 Pamekasan which refers to management functions namely planning, organizing, actuating, controlling; 2) Weaknesses and obstacles in the implementation of institutional cooperation at the adiwiyata madrasa internally and externally at MTs Negeri 2 Pamekasan; and 3) Ways to overcome weaknesses and obstacles in the implementation of institutional cooperation at the adiwiiyata madrasah internally and externally.